Answer:
1
Step-by-step explanation:
Simplifying
3x + 2(4x + -4) = 3
Reorder the terms:
3x + 2(-4 + 4x) = 3
3x + (-4 * 2 + 4x * 2) = 3
3x + (-8 + 8x) = 3
Reorder the terms:
-8 + 3x + 8x = 3
Combine like terms: 3x + 8x = 11x
-8 + 11x = 3
Solving
-8 + 11x = 3
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '8' to each side of the equation.
-8 + 8 + 11x = 3 + 8
Combine like terms: -8 + 8 = 0
0 + 11x = 3 + 8
11x = 3 + 8
Combine like terms: 3 + 8 = 11
11x = 11
Divide each side by '11'.
x = 1
Simplifying
x = 1
<span>(13a + 5b) + (a + 5b - 3)
</span><span>
= 13a + 5b + a + 5b - 3
= 14a + 10b - 3 </span>
Answer: 268.1
Step-by-step explanation:
V = (4/3) 3.14 (4) to the power of 3
here is your ans have a nice day